Letter - Winstanley, E.
032-0056-001 TELEGRAPHIC ADDRESS: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES: A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: Export.2968.ST/RN. Your Reference: 17th May, 1939. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We have this morning received an advice note from the Mansfield Shoe Company, Ltd., covering two cases delivered to Garston, for shipment to Rouen, under mark F.S.I. Nos.1-2. We observe that the packages are consigned "North Dock via Cockerell Siding". As we informed you yesterday, this is wrongly consigned, but we have been in touch with our Steamships Department, who have informed us that even though packages do come forward in this manner, provided they are consigned to the order of the C.W.S., Garston, no serious difficulty will be experienced. We also understand that one or two other packages are now lying at Garston, and, in order that we may control matters satisfactorily, we shall be glad if you will let us have a complete list of all the goods which will be going forward. Thanking you in anticipation, we remain, Yours faithfully, E. Winstanley, Export Department. 292/946/32/56